Metafora Kata â€œHatiâ€ dalam Bahasa Melayu Riau: Analisis Semantik Kognitif (The Metaphor of the Word â€œHatiâ€ (Heart) In Malay Language of Riau: Cognitive Semantics Analysis) - Hermandra Hermandra (Indonesian Language Education and Literature, 2022)
This study aims to examine the metaphor of the word "heart" in Riau Malay. This research is a qualitative descriptive study using cognitive semantic analysis. The research data comes from the speech of the Riau Malay people who use the metaphorical word "heart". Data was collected through interviews using fishing, tapping, listening and speaking techniques accompanied by recording techniques. The results of the study show that the metaphor of the word "heart" includes: small heart, big heart, broken heart, heart, fruit, eyes of heart, the heart of stone, solar plexus, conscience, hard heart, and rotten heart. This study describes the Malay community in producing speech using figurative language to make it look more polite. The use of figurative words can make the conversation more polite.Penelitian ini bertujuan untuk mengkaji metafora kata â€œhatiâ€ dalam bahasa Melayu Riau. Penelitian ini merupakan penelitian deskriptif kualitatif dengan menggunakan analisis semantik kognitif.Â Data penelitian berasal dari tuturan masyarakat Melayu Riau yang menggunakan ungkapan metafora kata â€œhatiâ€. Data dikumpulkan melaluiÂ wawancara dengan teknik pancing, sadap, dan simak libat cakap disertai dengan teknik rekam. Hasil penelitian menunjukkanÂ bahwaÂ metafora kata â€œhatiâ€, meliputi:Â kecil hati, besar hati, patah hati, jantung hati, buah hati, mata hati, hati batu, ulu hati, hati nurani, keras hati, dan busuk hati. Penelitian ini menggambarkan masyarakat Melayu dalam menghasilkan tuturan dengan menggunakan bahasa kias agar terlihat lebih santun.Â Penggunaan kata kias dapat menjadikan percakapan menjadi lebih sopan.